About Abdulla Qadiri's "Feast of the Jinns" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article uses the story "Feast of the jinns" by Abdulla Qodiriy as an example to tell about such creatures as "jinn" and "fairy". In addition, Nodar Dumbadze's work "Demons" and other works are also analyzed.